2018
DOI: 10.1016/j.geomorph.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Flow resistance, sediment transport, and bedform development in a steep gravel-bedded river flume

Abstract: Highlights: Flow resistance increased with shallow flow, bedforms, and high sediment transport intensity  Downstream and upstream migrating alternate bars developed on bed slopes up to 20%  Transition to upper plane bed coincided with development of concentrated sheetflow Abstract: Quantifying flow resistance and sediment transport rates in steep streams is important for flood and debris flow prediction, habitat restoration, and predicting how mountainous landscapes evolve. However, most studies have focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The existence of bedload transport pulses has been related to bedform migration (Gomez et al, 1989), a relationship that has been investigated in gravel‐bed flumes through experimental investigations into alternate bars (e.g. Dhont & Ancey, 2018; Palucis et al, 2018). When alternate bars are associated with near‐critical flows, antidunes may develop locally and contribute to sediment transport (see Movie S3 in Dhont & Ancey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of bedload transport pulses has been related to bedform migration (Gomez et al, 1989), a relationship that has been investigated in gravel‐bed flumes through experimental investigations into alternate bars (e.g. Dhont & Ancey, 2018; Palucis et al, 2018). When alternate bars are associated with near‐critical flows, antidunes may develop locally and contribute to sediment transport (see Movie S3 in Dhont & Ancey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Being somewhat different from that in the idling tests (Table 2), gear‐specific P fluctuates when the rotor operates at a certain gear in the tested mixture. This should be in relation to the fundamental granular nature of the slurries (debris flows) (Coussot & Ancey, 1999; Palucis et al, 2018). On the other hand, the standard deviation of 27 P time series for nine runs is on the order of only 0.99–9.77 W. It shows that P is essentially to remain roughly constant during the individual stages of each run, given the magnitudes of the mean values of the series of P ( P avg ), ranging from 236.61 to 337.45 W. Therefore, stepped vertical ascending pattern of the plots of P versus t is still significant.…”
Section: Resultsmentioning
confidence: 99%
“…This higher flow velocity results in reduced runoff depth, lower pressure difference in the vortex area behind the vegetation, decreased potential energy, and critical initial runoff energy. As a consequence, the kinetic energy and power of the runoff are enhanced, leading to increased soil loss (Li et al, 2022; Palucis et al, 2018; Papanicolaou et al, 2018). Consistent with this study, Zhang et al (2018) demonstrated that the change in slope gradient directly affects slope runoff energy.…”
Section: Discussionmentioning
confidence: 99%